Spinal and corticospinal excitability changes with voluntary modulation of motor cortex oscillations - Ioana Susnoschi Luca; Aleksandra Vuckovic (NeuroImage)
Aim: The aim of this study was to investigate the effects of EEG neurofeedback (NF)-induced modulation of sensorimotor alpha (i.e., mu) rhythm on spinal and corticospinal tract (CST) excitability. Methods: Forty-three healthy volunteers participated in 3 sessions of EEG-NF for upregulation (N=24) or downregulation (N=19) of individual alpha oscillations at central location Cz. Spinal excitability was studied before and during NF using H-reflex of the soleus muscle, and CST excitability was tested before and after NF, through Motor-Evoked Potential (MEP) of the tibialis anterior muscle. Mu rhythm was extracted using current source density. Differences in MEP and H-reflex before and during/after NF were analysed using repeated measures analysis. The relationship with motor cortexcortical excitability was estimated through linear regression between change in MEP/H-reflex, and change in power of mu rhythm and the upper portion of mu rhythm, muh. Results: CST excitability changes were significantly correlated to change in muh (p-value < 0.044, |r|>0.42), while spinal excitability changes were correlated to broad mu power modulation (p-value < 0.04, |r| > 0.43). While no distinct effect of NF on spinal versus CST excitability was found, the correlations indicate an inverted U-shape relationship between cortical and subcortical excitability. The trends of the correlations between spinal/CST excitability change and EEG power change were preserved when participants were grouped by success at NF task, and by mu modulation outcome, indicating that the net effect of power change at Cz weighs more than the task the participants attempted to accomplish. Conclusions: The consistent direction of mu power correlation with both MEP, tested after NF, and H-reflex, tested during NF, indicates that modifications in mu activity are associated with spinal and CST adaptations lasting beyond the NF session, evidencing neuroplasticity. Together with the inverted U-shape relationship found between amplitude of mu modulation and spinal/CST excitability change, the results provide support for further research and clinical implementation of NF to induce CNS plasticity, a prerequisite for effective neural rehabilitation.